IATROGENIC PROSTHODONTICS IMPACT ON OCCLUSAL AND TMJ DYSFUNCTIONS - George Luca; Sever Popa (Romanian Society of Oral Rehabilitation, 2014)
Introduction Occlusal disharmonies might be quite challenging especially when considered in a very strict aesthetic context. This is especially true when dealing with multiple periodontal problems, carious disease, in combination with incorrect occlusal relationship, extruded or migrated teeth and vicious habits. In these cases a complete examination, comprising clinical and paraclinical exam (simulator, X-rays etc.), is mandatory. Aim of the study The present study focused on evaluating the iatrogenic impact of prosthodontic restorations on occlusion relationship and TMJ. Material and methods In order to assess the oral status of the patients in the study group a thorough history, combined with a specific clinical examination and complementary tests were performed. All results were recorded in specific patient charts. All the factors that may interfere with physiological functionality of maxillary system were taken into account. Results The study group comprised 132 patients (69 women, 63 men), aged 20-61, with different types of prosthodontic restorations. 68.18% of patient had fixed prosthodontics and 31.82% combined - fixed prosthodontics and removable partial dentures. 47.27% of patient had occlusal dysfunction. A higher percentage of occlusal and TMJ dysfunctions was recorded in patients with combined - fixed and removable prosthesis (61.20% of patients with combined restorations versus 43.58% of patients with fixed prosthodontics). Conclusions Prosthodontic restorations cannot be limited to clinical and technological standard paths. No matter how well the restoration is done, it must overcome the challenge of been accepted by the patient, or it depends greatly on the ability of the practitioner to understand the patient's expectations, and in carrying out the treatment accordingly to patient's personality.